2015
DOI: 10.1063/1.4921896
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state of anhydrous AlF3 and AlI3: Modeling of extreme condition halide chemistry

Abstract: Pressure dependent angle-dispersive x-ray powder diffraction measurements of alpha-phase aluminum trifluoride (α-AlF3) and separately, aluminum triiodide (AlI3) were conducted using a diamond-anvil cell. Results at 295 K extend to 50 GPa. The equations of state of AlF3 and AlI3 were determined through refinements of collected x-ray diffraction patterns. The respective bulk moduli and corresponding pressure derivatives are reported for multiple orders of the Birch-Murnaghan (B-M), finite-strain (F-f), and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…According to Morelock et al, aluminum trifluoride adopts a cubic form above 440 °C, which upon cooling changes to a rhombohedral phase. The X-ray diffraction (XRD) analysis of about 11 nm AlF X [O] layer revealed the rhombohedral phase (see the Supporting Information S4) and is thus consistent with the literature. On the contrary, at 400 °C, the thickness of the fluorinated layer stayed around 3 nm even after prolonged total NbF 5 exposure of 2700 s. Chen et al showed the fluoride ions penetrating up to 2 nm thick aluminum oxide after treating fluorinated alumina at 400 °C, and neutral/ion beams-assisted fluorination lead to a thicker AlF X [O] layer . Moreover, up to 0.5 nm thick AlF 3 layer was obtained at a lower temperature of 300 °C with HF as a fluorinating agent .…”
Section: Resultssupporting
confidence: 82%
“…According to Morelock et al, aluminum trifluoride adopts a cubic form above 440 °C, which upon cooling changes to a rhombohedral phase. The X-ray diffraction (XRD) analysis of about 11 nm AlF X [O] layer revealed the rhombohedral phase (see the Supporting Information S4) and is thus consistent with the literature. On the contrary, at 400 °C, the thickness of the fluorinated layer stayed around 3 nm even after prolonged total NbF 5 exposure of 2700 s. Chen et al showed the fluoride ions penetrating up to 2 nm thick aluminum oxide after treating fluorinated alumina at 400 °C, and neutral/ion beams-assisted fluorination lead to a thicker AlF X [O] layer . Moreover, up to 0.5 nm thick AlF 3 layer was obtained at a lower temperature of 300 °C with HF as a fluorinating agent .…”
Section: Resultssupporting
confidence: 82%
“…Let us introduce the MX 3 perovskites we considered in this study, focusing on their structures and the geometric peculiarities of their important vacant A-sites where the helium atom may be stuffed. AlF 3 , GaF 3 , and InF 3 belong to the VF 3 -type materials family crystallizing in the R 3̅ c space group. , Experiments revealed this rhombohedral structure remains the ground state up to 50 GPa for AlF 3 and 28 GPa for GaF 3 . Comparison of the enthalpy calculated for R 3̅ c -AlF 3 with the enthalpies of other known stable and metastable polymorphs that can be made at high temperatures or using molecular templates , revealed that it was the preferred geometry at both 0 and 10 GPa (Table S4).…”
Section: Resultsmentioning
confidence: 94%
“…This polytype is more commonly encountered in triuorides. In this context, it is of interest to explore the high-pressure phase transformations of TeO 3 , and compare them with those of triuorides, [24][25][26] and trioxides, in particular, WO 3 , [27][28][29][30][31] and ReO 3 itself. [32][33][34][35] Here we present a combined experimental (Raman scattering) and theoretical (DFT modelling) study on the inuence of high pressure on the structure stability of TeO 3 .…”
Section: Introductionmentioning
confidence: 99%